A photovoice study on early career EFL teachers’ professional identity construction in Indonesian Islamic primary schools - Ali, Fachri; Akbar, Reza Adinul; Dewi, Yulianita Listya (Erudita: Journal of English Language Teaching, 2025)
Even though teacher identity has been globally investigated by previous researchers, early career teacher professional identity construction receives scanty attention. To fill this void, the present photovoice study aims to explore how EFL teachers construct their professional identities during their early career of teaching in Islamic primary schools. Designed in participatory visual research, two early career EFL teachers in Indonesian Islamic primary schools were recruited to participate. Data were collected through photovoice method and analyzed adapting thematic analysis. Study findings demonstrate that the EFL teachers portrayed their practiced identities in their early career. These teacher identities covered teaching-practices and methodologies, socio-cultural context, teacher-student relationship, professional development and support, and personal reflections. The study carries implications for teacher education programs and the professional development of EFL educators in Islamic primary schools. Recognizing the importance of cultural and religious dimensions in teacher identity development, teacher training programs should incorporate strategies to prepare early career teachers for the professional identity construction posed by Islamic educational settings.